Regulation of the Actin Cytoskeleton-Plasma Membrane Interplay by Phosphoinositides - Saarikangas, Juha; Zhao, Hongxia; Lappalainen, Pekka (Physiological reviews, 2010)
Program in Cell and Molecular Biology, Institute of Biotechnology, University of Helsinki, Helsinki, Finland The plasma membrane and the underlying cortical actin cytoskeleton undergo continuous dynamic interplay that is responsible for many essential aspects of cell physiology. Polymerization of actin filaments against cellular membranes provides the force for a number of cellular processes such as migration, morphogenesis, and endocytosis. Plasma membrane phosphoinositides (especially phosphatidylinositol bis- and trisphosphates) play a central role in regulating the organization and dynamics of the actin cytoskeleton by acting as platforms for protein recruitment, by triggering signaling cascades, and by directly regulating the activities of actin-binding proteins. Furthermore, a number of actin-associated proteins, such as BAR domain proteins, are capable of directly deforming phosphoinositide-rich membranes to induce plasma membrane protrusions or invaginations. Recent studies have also provided evidence that the actin cytoskeleton-plasma membrane interactions are misregulated in a number of pathological conditions such as cancer and during pathogen invasion. Here, we summarize the wealth of knowledge on how the cortical actin cytoskeleton is regulated by phosphoinositides during various cell biological processes. We also discuss the mechanisms by which interplay between actin dynamics and certain membrane deforming proteins regulate the morphology of the plasma membrane.